Lebak Swamp Typology and Rice Production Potency in Jakabaring South Sumatra - Elisa Wildayana; M. Edi Armanto (Agriekonomika, 2018)
The research aimed to compare lebak swamp typology and rice production potency before and after landfills in Jakabaring South Sumatra.  This study is a qualitative and quantitative research assisted with interpretation of Landsat images in 1987 and 2015. The research method was survey method in the fields and respondents were taken by randomly purposive sampling and by using open questionnaire. The research resulted that lebak swamp in Jakabaring can be divided into six typologies, namely lebak lebung, deep lebak, middle lebak, levee lebak, shallow lebak and dry land. After landfills, dry land covers an area of 1,964 ha (72.73%), while the lebak swamp was decreased by approximately 736 ha (27.27%). Before landfills, soil orders were found based on its dominance, namely Histosols, Entisols, Inceptisols and Gelisols. After landfills, composition of soil order is dominated by Entisol, Inceptisol, Gelisols and Histosols. Before landfills rice yields were produced about 3,240 tons of milled dry rice (MDR)/year, and potency rice production is now only about 506.25 tons of MDR/year.